Język rosyjski jako centrum idei narodowej – ujęcie Władymira Biblera - Krzysztof Kropaczewski (Studia Rossica Posnaniensia)
An article written by a famous Russian humanist Vladimir Bibler, entitled “Russian national idea: Russian native tongue and the experience of culturological assumptions” (Национальная русская идея? – Русская речь. Опыт культурологического предположения), is discussed here in the context of Russian culture’s logocentricity and the related phenomenon of Russian philosophy, with language and a word being its “core elements”. Bibler perceives his native tongue not only as a fundamental element of Russian mentality or “world view”, but also as a dynamic, nationwide symbol as well as the central element – an idea capable of uniting the whole society and fostering the relationship between tradition and the future.